INTERPRETATION OF THE FEMALE IMAGE IN NARRATIVES OF TURKIC PEOPLES - Bekchanova Sayyara Bazarbaevna (International Journal of Literature and Language Studies, 2026)
This article focuses on the image of women in Turkic proverbs and their analysis. The characteristics of the female image are formed on the basis of events reflected in the national customs and lifestyle of each nation. While female characters are embodied in various forms, as merciless, jealous characters, in another aspect, they are portrayed as loving mothers who are ready to do anything for their child. It was these issues that were analyzed using parables.